(untitled) (Baghdad Science Journal, 2011)
The study was carried out in order to evaluate clinically and laboratory cachectic animals suffering from anemia. Animal examined were 50 cow and calf. The study include clinical, hemato and biochemical test for accurate diagnosis of cachexia in cows and calves . Blood smears were conducted for detection of blood parasites , fecal examination for gastrointestinal parasites and Different parameters were applied for classification of cachexia , depending on bony projection specially ribs and pelvic and generalized muscular atrophy. However , The study revealed an incidence of cachexia and anemia of blood parasites was including Theileria, Anaplasma, gastrointestinal parasites, ten cases were shown foreign body syndrome while other tens were diagnosed as other clinical cases. A significant decrease ( P < 0.05) of RBCS, Hb, PCV and WBC count in debility animals were observed . However , a significant lymphocytosis were seen in blood parasites infection and other clinical cases , Neutrophilia in foreign body syndrome and other clinical cases , Esenophilia in gastrointestinal parasites infestation ,Monocytosis in all clinical cases were detected . Different parameters were applied for classification of anemia mainly morphological classification including macrocytic hypochromic anemia mainly recorded in blood parasites infection and other clinical cases while Normocytic hypochromic anemia appeared in gastrointestinal parasites infestation, and foreign body Syndrome.Fecal examination of cachectic animal indicate the identification of (7) species of gastrointestinal parasites including: Cooperia onchophora, Haemonchus contortus, Bunostomum phlebtomum, Ostertagia spp., Oesophagostomum radiatum, Trichostrongylus axei and Strongyloides papillosus. However , a mixed infestation parasite was dominant and recorded in Animal.Biochemical changes revealed a. Hypoprotenemia appears in all cachectic animal except in foreign body syndrome cases .